2000
DOI: 10.1590/s0100-204x2000001000024
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de nutrientes em vertissolo calcário

Abstract: EVALUATION OF NUTRIENTS IN A CALCAREOUS VERTISOLABSTRACT -The capacity of calcareous Vertisol to supply nutrients for the growth of rice plants was studied. The method of subtraction diagnostic was adopted in this study. A completely randomized experimental design with nine treatments (complete, control, minus P, minus S, minus B, minus Cu, minus Fe, minus Mn and minus Zn) and three replicates were used. The amount of the dry matter of the rice was ranked in the following decreasing order of treatments: comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…These conditions widely interfere with the ion adsorption and solubilization processes, which are responsible for the concentration of nutrients in the soil solution (Moreira et al, 2000). P precipitation, with the formation of calcium phosphate, is one of the reasons for the reduction of this element in the soil solution.…”
Section: Resultsmentioning
confidence: 99%
“…These conditions widely interfere with the ion adsorption and solubilization processes, which are responsible for the concentration of nutrients in the soil solution (Moreira et al, 2000). P precipitation, with the formation of calcium phosphate, is one of the reasons for the reduction of this element in the soil solution.…”
Section: Resultsmentioning
confidence: 99%
“…Certamente um dos elementos que contribuem na instabilidade na área da dfv diz respeito às peculiaridades químicas dos solos carbonáticos. Entre elas está a diminuição da disponibilidade de alguns micronutrientes (MOREIRA et al, 2000). O excesso de cálcio pode aumentar a precipitação de fósforo, diminuindo sua disponibilidade para as plantas, além de inibir a absorção de alguns micronutrientes (MOREIRA et al, 2000), difi cultando o estabelecimento e a regeneração da vegetação.…”
Section: Discussionunclassified
“…Apodi Plateau, Mota et al (2007) found quartz, goethite, hematite, and magnetite. In a Cambissolo Háplico (Inceptisol), Moreira et al (2000) detected quartz, orthoclase, pyroxene, ilmenite, and small amounts of kaolinite, hematite, and goethite. Calcite was not found in these two studies.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…According to the Brazilian Soil Classification System -SiBCS (Santos et al, 2013), the main diagnostic feature in soils on karstic landscapes are carbonate or hypocarbonate properties, and calcic and petrocalcic diagnostic horizons. In these horizons, carbonate accumulation influences chemical characteristics such as pH, soil buffering, cation exchange capacity (CEC), and nutrient availability to plants (Moreira et al, 2000;Khresat, 2001). In addition, morphological characteristics such as continuous cementation may occur as the process of calcification advances.…”
Section: Introductionmentioning
confidence: 99%